1995
DOI: 10.1002/eji.1830251205
|View full text |Cite
|
Sign up to set email alerts
|

Lack of inducible nitric oxide synthase activity in T cell clones and T lymphocytes from naive and Leishmania major‐infected mice

Abstract: Nitric oxide (NO) generated by the inducible isoform of nitric oxide synthase (iNOS) is implicated in a number of immunological processes including killing of intracellular parasites, suppression of T cell proliferation, production of cytokines and destruction of tissue in autoimmune diseases. Considering that cytokine-activated mouse macrophages, fibroblasts and endothelial cells are potent producers of NO, we investigated whether T cells, as central participants in immune responses, can also be activated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
(13 reference statements)
2
9
0
Order By: Relevance
“…1, NO production could be augmented by addition of splenic T cells to levels similar to that induced by IFN-␥ and LPS. On the other hand, T cells incubated without macrophages failed to produce NO (data not shown), confirming previous reports that T cells do not produce NO (39). To define the optimal T cell/macrophage ratio for activation, we cocultured bone marrow-derived macrophages with increasing numbers of naive anti-CD3-treated T cells.…”
Section: Tnfrp55p75supporting
confidence: 86%
“…1, NO production could be augmented by addition of splenic T cells to levels similar to that induced by IFN-␥ and LPS. On the other hand, T cells incubated without macrophages failed to produce NO (data not shown), confirming previous reports that T cells do not produce NO (39). To define the optimal T cell/macrophage ratio for activation, we cocultured bone marrow-derived macrophages with increasing numbers of naive anti-CD3-treated T cells.…”
Section: Tnfrp55p75supporting
confidence: 86%
“…2E). This is in line with the lack of NOS2 in these cells (25). Thus, NOS2-derived NO is required for the activation of NK cells, but not T cells, by IL-12.…”
supporting
confidence: 82%
“…In the mouse, Thl cells can be activated to produce large amounts of NO which can inhibit the secretion of IL-2 and IFN-7 by Thl cells, thus acting as an autoregulator of the immune response [27] and possibly altering the balance of Thl and Th2 cells. However, others have been unable to demonstrate T-cell synthesis of NO [28]. B-cells may also be a source of NO, and in humans it has been reported that Epstein-Barr virus-transformed B-cells and cell lines from Burkitt's lymphoma express iNOS [29].…”
Section: No In the Generation Of The Immune Responsementioning
confidence: 99%